Differences in incidence and fatality of COVID‐19 by SARS‐CoV‐2 Omicron variant versus Delta variant in relation to vaccine coverage: A world‐wide review. Issue 1 (20th September 2022) - Wang, Chao; Liu, Bei; Zhang, Sihui; Huang, Ninghua; Zhao, Tianshuo; Lu, Qing‐Bin; Cui, Fuqiang
Abstract: We aim to evaluate the evolution differences in the incidence and case fatality rate (CFR) of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) Delta and Omicron variants. The average incidence and CFRs were described between different countries. A gamma generalized linear mixed model (GLMM) was used to compare the CFRs of Delta and Omicron variants based on vaccination coverage. Totally, 50 countries were included for analyses. The incidence of coronavirus disease 2019 (COVID‐19) ranged from 0.16/100, 000 to 82.95/100, 000 during the Delta period and 0.03/100, 000 to 440.88/100, 000 during the Omicron period. The median CFRs were 8.56 (interquartile range [IQR]: 4.76–18.39) during the Delta period and 3.04 (IQR: 1.87–7.48) during the Omicron period, respectively. A total of 47 out of 50 countries showed decreased CFRs of the Omicron variant with the rate ratio ranging from 0.02 (95% confidence interval [CI]: 0.01–0.03) (in Cambodia) to 0.97 (95% CI: 0.87–1.08) (in Ireland). Gamma GLMM analysis showed that the decreased CFR was largely a result of the decreased pathogenicity of Omicron besides the increased vaccination coverage. The Omicron variant shows a higher incidence but a lower CFR around the world as a whole, which is mainly a result of the decreased pathogenicity by SARS‐CoV‐2's mutation, while the vaccination against SARS‐CoV‐2 still acts as a valuable measure in preventing people from death.